2018
DOI: 10.1007/s11325-018-1760-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of fractional exhaled nitric oxide and nasal nitric oxide in male patients with obstructive sleep apnea

Abstract: Objective Airway inflammation plays an important role in obstructive sleep apnea (OSA); exhaled nitric oxide is regarded as a noninvasive marker of airway inflammation. The aim of this study was to evaluate fractional exhaled nitric oxide (FeNO) and nasal nitric oxide (nNO) in patients with OSA. Methods Seventy-five patients with OSA and 30 health controls were enrolled in this study. FeNO and nNO were measured before and after sleep. Nasal lavage was performed in 31 no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Even the association of the eNO with the apnea-hypopnea index (AHI) is controversial. Indeed, while some studies found a strong and positive correlation between FeNO and AHI, with a r of 0.8–0.9 [23,33], or oNO and AHI ( r : 0.46) [32] and a negative one between CaNO and AHI, with a r of 0.9 [23], this was not confirmed by other studies [20,21,22,27,28,39,41].…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Even the association of the eNO with the apnea-hypopnea index (AHI) is controversial. Indeed, while some studies found a strong and positive correlation between FeNO and AHI, with a r of 0.8–0.9 [23,33], or oNO and AHI ( r : 0.46) [32] and a negative one between CaNO and AHI, with a r of 0.9 [23], this was not confirmed by other studies [20,21,22,27,28,39,41].…”
Section: Resultsmentioning
confidence: 83%
“…The study of FeNO in the diagnosis of OSAS has led to contradictory findings. Indeed, while some studies described a raising of FeNO level in OSAS [20,21,22,23,24,25], the majority did not confirm the finding [26,27,28,29,30] or just showed a higher concentration in OSAS patients when compared with non-obese healthy controls [31,32,33]. Besides, even considering only those studies with a positive finding, the FeNO level, albeit statistically higher than healthy controls, did not reach a clinical significance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sputum gene expression analyses have identified a significant increase for IL-6 and IL-8 in IPF patients [30]. Both IL-6 and IL-8 may mediate nasal inflammation in OSA patients, and were positively correlated with AHI [31]. Another possible explanation is that pulmonary function tests in identified studies were performed in an upright position but not in a supine position, which could not accurately reflect pulmonary function changes during sleep [13,23,26].…”
Section: Plos Onementioning
confidence: 99%
“…Many studies have investigated eNO behavior in patients with obstructive sleep apnea (OSA), reporting slightly, but still significantly higher levels of FeNO and J’awNO and, conversely, reduced CaNO values than healthy controls [ 94 , 95 , 96 ]. Interestingly, c-PAP therapy led to a normalization of eNO parameters, suggesting its potential role as a biomarker of compliance and response to therapy [ 97 , 98 ].…”
Section: Comorbidities/complications Of Ilds: a Pitfall For Eno Anmentioning
confidence: 99%